Verification of the Effectiveness of Occlusal Treatment Using Postural Information: A Case Report - Jeannin, DDS, PhD, HDR, Christophe; Bellemon, Gwennaëlle; Moreno, Matthieu; Gebeile-Chauty, DDS, PhD, Sarah (International Journal of Innovative Research in Medical Science, 2022)
Occlusal treatments can cause irreversible dental changes without guaranteeing clinical success. To avoid this, an initial, non-mutilating, phase of treatment using splint, for example, followed by an objective evaluation of the effectiveness is required before moving to next phase that permanently freezes the new mandibular position. As an example, a 74 years-old European female who consulted for tinnitus was referred, prior to any procedure, to a posturologist who established an initial postural assessment. A splint was made to increase the height between posterior teeth. 6 months after the tinnitus had disappeared, the patient was sent for postural assessment (made by the same posturologist and using the same tests). After an additional increase in posterior teeth height validated by an additional postural analysis, new fixed prostheses were placed taking into account the respective increases in height validated during this initial phase of treatment. Monitoring the effectiveness of initial and reversible stage is important as in occlusodontology, the disappearance of clinical symptoms is not always synonymous with healing. Moreover this is an interesting way to improve the rigor of patient management.